2002
DOI: 10.1046/j.0021-8782.2002.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural analysis of pancreatic acinar cells from mice fed on genetically modified soybean

Abstract: No direct evidence that genetically modified (GM) food may represent a possible danger for health has been reported so far; however, the scientific literature in this field is quite poor. Therefore, we investigated the possible effects of a diet containing GM soybean on mouse exocrine pancreas by means of ultrastructural, morphometrical and immunocytochemical analyses. Our observations demonstrate that, although no structural modification occurs in pancreatic acinar cells of mice fed on GM soybean, quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 28 publications
3
36
0
Order By: Relevance
“…Factors such as pH and pepsin-to-substrate ratio greatly influence the digestion of Cry1Ab proteins suggesting that an in-vitro digestibility test that is new and more physiologically relevant should be involved such that the resistance of a protein to digestion can be studied (Guimaraes et al, 2010). For example, a research group found that significant modifications of some nuclear features in hepatocyte nuclei (Malatesta et al, 2002a) and influence zymogen synthesis and processing in mouse pancreatic acinar cells after mice were fed GM soybean (Malatesta et al, 2002b). Moreover, they reported a significant lowering of nucleoplasmic and nucleolar splicing factors as well as accumulation of perichromatin granules in GM-fed mice (Malatesta et al, 2003).…”
Section: Possible Mechanisms For Gm Effects On Animalsmentioning
confidence: 99%
“…Factors such as pH and pepsin-to-substrate ratio greatly influence the digestion of Cry1Ab proteins suggesting that an in-vitro digestibility test that is new and more physiologically relevant should be involved such that the resistance of a protein to digestion can be studied (Guimaraes et al, 2010). For example, a research group found that significant modifications of some nuclear features in hepatocyte nuclei (Malatesta et al, 2002a) and influence zymogen synthesis and processing in mouse pancreatic acinar cells after mice were fed GM soybean (Malatesta et al, 2002b). Moreover, they reported a significant lowering of nucleoplasmic and nucleolar splicing factors as well as accumulation of perichromatin granules in GM-fed mice (Malatesta et al, 2003).…”
Section: Possible Mechanisms For Gm Effects On Animalsmentioning
confidence: 99%
“…Excessive stimulation of pancreatic acinar cells activates trypsin synthesis and the production of cytokines, both of which result in cellular damage [79]. Acinar cell damage has been implicated in glyphosate exposure in multiple studies involving rodents [80], and acinar cell carcinoma is the second most common type of pancreatic cancer [81]. The incidence of pancreatic cancer is sharply on the rise in step with glyphosate usage on corn and soy crops (R = 0.918, p < 4.6E−7) [32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hepatocytes of GM-fed mice showed mitochondrial and nuclear modifications indicative of reduced metabolic rate. In previous studies on hepatocytes from young and adult (2-8 months of age) female mice fed GM soybeans, nuclear modifications involving structural constituents of the transcription and splicing properties pathways were seen (Malatesta et al, 2002a). Although the cause(s) of the observed alterations could not be conclusively established, it was noted that these modifications disappeared when GM soybean was replaced by a non-GM one in the diet (Malatesta et al, 2005).…”
Section: Effects On Animal Health Of Gm Soybeanmentioning
confidence: 97%